Caching Strategies Based on Data Density Estimation in Mobile Ad-hoc Networks - Bhaskar, Bandi; Mahesh, Dandugudum.; Kumaraswamy, Palleboina.; Nagender, Yamsani. (International Journal of Engineering and Technology, 2018)
Current data caching technique not only for additional networks with p2p nodes distributing metadata items. Our primary objective would be to implement a new asymmetrical mutually beneficial cache campaign strategy, in which many metadata appeals are actually interesting conveyed to anything other than the cache layer on each and every node, but perhaps metadata replies could perhaps really be communicated cache layer, even to the optimal nodes that would have to be cached. This solution not only reduces overhead to replicate data between user spaces Â Yet another intention of this same paper is to introduce the MAODV and ODMRP algorithms for the new disproportionate supportive cache method where it calculate the two routing protocols proposed, namely MAODV and ODMRP, for performance - based wireless ad hoc networks. This same paper examines the overall performance of two controversial ad hoc network multicast protocols: MAODV and ODMRP. MAODV continues to build and retains a hard state - based multicast tree, ODMRP maintains a soft state - based mesh. Even our own results demonstrate in numerous situations ODMRP attains a higher packet delivery ratio, nonetheless outcomes in much higher overheads.Â Â Â